Imposing choice on the uninformed: The case of dynamic currency conversion - Christian Ewerhart; Sheng Li (University of Zurich, Department of Economics, 2023)
Over the course of the past two decades, it has become a common experience for consumers authorizing an international transaction via credit card to be invited to choose the currency in which they wish the transaction to be executed. While this choice, made feasible by a technology known as dynamic currency conversion (DCC), seems to foster competition, we argue that the opposite is the case. In fact, the unique pure-strategy equilibrium in a natural fee-setting game, with uninformed and possibly inattentive consumers, turns out to be highly asymmetric, entailing fees for the service provider that persistently exceed the monopoly level. Although losses in welfare may be substantial, a regulatory solution is unlikely to come about due to a global free-rider problem.
Keywords: D21; G21; G28; G53; 330; Dynamic currency conversion; Credit cards; Price competition; Monopoly; Free-rider problem; Rational inattention